Mangan Barema Tradition for Productive Values in Elementary Character Education - Ulandari, Sri; Muhdar, Syafruddin; Bilal, Arpan Islami (Universitas prof. Dr. Moestopo (Beragama), 2026)
The Mangan Barema tradition is a communal cultural practice carried out by the people of Sumbawa that reflects values of cooperation, equality, and social responsibility. Despite the growing attention to local wisdom and character education, limited studies have examined how specific cultural traditions function as ethnopedagogical learning systems that contribute to character formation. This study aims to analyze the implementation of the Mangan Barema tradition and to identify the productive values embedded in the practice in relation to elementary school character education. This research employed a qualitative descriptive approach, using participant observation, in-depth interviews with community leaders and local residents, and documentation analysis. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that the Mangan Barema tradition embodies productive values such as cooperation, responsibility, equality, discipline, and social solidarity through collective activities including food preparation, ritual processions, and communal dining. These activities function as participatory learning processes that reinforce moral awareness and social responsibility among participants. The study concludes that the Mangan Barema tradition represents a form of community-based character education that supports the development of students’ social and moral values through culturally grounded learning practices.